International review of neurobiology. (International review of neurobiology, 1992)
Published since 1959, this serial presents in-depth reviews of key topics in neuroscience, from molecules to behavior. The serial stays keenly atuned to recent developments through the contributions of first-class experts in the many fields of neuroscience. Neuroscientists as well as clinicians, psychologists, physiologists and pharmacoloists will find this serial an indispensable addition to their library.